Novel Method to Synthesize Conducting Polyaniline/nickle Sulphide Nanocomposite Films and the Study of their Structural and Electrical Properties. (2015) - Batool, Aisha; Kanwal, Farah; Riaz, Saira; Abbas, Aamir; Naseem, Shahzad
Abstract: Different methodologies and routes have been adopted to enhance compatibility and applications of conjugated polymers since two decades. In this project we have adopted a novel method to synthesize polyaniline nanocomposite films with different weight percentages of nickel sulphide nanoparticles. These nanocomposite films were than subjected to various characterizations such as X-ray diffraction analysis, scanning electron microscopy (SEM), and standard four probe method to study the effect of various weight percentages of nanoparticles on structural and electrical properties.